P156 Efficacy, safety and tolerability of once-daily tiotropium respimat® add-on therapy in children with moderate symptomatic asthma. (15th November 2016) - Schmidt, O; Hamelmann, E; Vogelberg, C; Laki, I; Azzi, G El; Engel, M; Moroni-Zentgraf, P; Finnigan, H; Vandewalker, M
Abstract : Introduction and objectives: A Phase II trial has shown that tiotropium Respimat® (tioR) is an effective, safe, and well-tolerated bronchodilator in patients aged 6–11 years with moderate symptomatic asthma. 1 To further assess the efficacy and safety of once-daily tioR add-on therapy, a Phase III trial was carried out in patients aged 6–11 years with moderate symptomatic asthma. Methods: This 48-week, Phase III, randomised, double-blind, placebo-controlled, parallel-group study (CanoTinA-asthma®; NCT01634139 ) was performed in patients aged 6–11 years with moderate symptomatic asthma. Patients received once-daily tioR 5μg (2 puffs, 2.5 µg), tioR 2.5 μg (2 puffs, 1.25 µg) or placebo Respimat® (pboR; 2 puffs) as add-on to maintenance treatment of at least medium-dose inhaled corticosteroid (ICS) (200–400 µg budesonide or equivalent) alone or in combination with another controller medication. The primary end point was peak FEV1 within 3 hours post-dosing (FEV1(0–3 h)). Secondary end points included trough FEV1 (key end point), FEV1 area under the curve (AUC) (0–3 h), and peak FVC (0–3 h); all measured as response (change from baseline) at Week 24. Adverse events (AEs) were analysed descriptively. Results: Of 403 patients randomised, 401 were treated. Baseline demographics and disease characteristics were balanced between treatment groups. TioR 5 µg and 2.5 µg provided statistically significant improvements in lung function versus pboR at Week 24 (Table) with adjusted mean difference ± standard error peak FEV1 (0–3 h) improvements of 164 ± 31 ml (p < 0.0001) and 170 ± 31 ml (p < 0.0001), respectively. The frequency of patients with AEs was similar across treatment arms, with a low incidence of drug-related and serious AEs (Table); no deaths occurred. The most common AEs were asthma worsening/exacerbation (lower incidence in tioR 5µg and 2.5 µg [34.1% and 36.3%] vs pboR [43.5%]), decreased peak expiratory flow rate (21.5% and 23% vs 20.6%), nasopharyngitis (8.9% and 11.1% vs 9.9%) and respiratory tract infection (9.6% and 8.1% vs 12.2%). Conclusion: In patients aged 6–11 years with moderate symptomatic asthma, once-daily tioR add-on to ICS with or without other maintenance therapy significantly improves lung function compared with pboR. The safety profile of tioR was similar to that of pboR. Reference: Vogelberg C, et al . Respir Res 2015;16 (1):20. Please refer to page A272 for declarations of interest in relation to abstract P156.